Evaluation of the Effects of Pinus koraiensis Needle Extracts on Serum Lipid and Oxidative Stress in Adults with Borderline Dyslipidemia: A Randomized, Double-Blind, and Placebo-Controlled Clinical Trial. (16th August 2016) - Lee, Hansongyi; Kim, Hyerang; Choue, Ryowon; Lim, Hyunjung
Abstract : Background. Dyslipidemia has been well-known as a common metabolic disorder contributing to cardiovascular disease. The aim of this study was to evaluate the effect of the Pinus koraiensis needle extracts (PKE) on the blood cholesterol and oxidative stress. Method. We conducted a 12-week randomized, double-blinded controlled trial to examine the effect of PKE on blood lipid profiles in adults with borderline dyslipidemia. Thirty-three eligible persons were recruited and randomly assigned into PKE (n = 20 ) and placebo groups (n = 13 ). Serum lipids including total cholesterol, low-density lipoprotein- (LDL-) cholesterol, high-density lipoprotein- (HDL-) cholesterol, very low-density lipoprotein- (VLDL-) cholesterol, and triglyceride were measured before and after trial. Serum insulin, glucose, and antioxidant indicators were also analyzed before and after trial and anthropometry and blood pressure were measured every 4 weeks. Results. After 12 weeks, PKE statically significant decreases in systolic blood pressure (p < 0.05 ) and waist circumference (p < 0.05 ) were observed. Also, VLDL-cholesterol significantly decreased (from24.4 ± 10.0 mg/dL at baseline to18.4 ± 4.1 mg/dL after 12 weeks) (p < 0.05 ) and superoxide dismutase (SOD) increased (6.12 ± 0.41 U/mL to9.06 ± 0.62 U/mL) (p < 0.01 ) in PKE group. However, after adjustment with WC, VLDL-cholesterol was not significant between groups (p = 0.095 ) and while SOD remained significant between groups (p = 0.013 ). Conclusion. The results show that PKE was effective in improving the superoxide dismutase in the individuals with borderline dyslipidemia.